Understanding the Nano-bio Interfaces: Lipid-Coatings for Inorganic Nanoparticles as Promising Strategy for Biomedical Applications - Luchini, Alessandra; Vitiello, Giuseppe (Frontiers in Chemistry, 2019)
Inorganic nanoparticles (NPs) exhibit relevant physical properties for application in biomedicine and specifically for both the diagnosis and therapy (i.e. theranostic) of severe pathologies, such as cancer. The inorganic NP core is often not stable in aqueous suspension and can induce cytotoxic effects. For this reason, over the years, several coating strategies were suggested to improve the NP stability in aqueous solutions as well as the NP biocompatibility. Among the various components which can be used for NP coatings, lipids, and in particular phospholipids emerged as versatile molecular building blocks for the production of NP coatings suitable for biomedical application. The recent synthetic efforts in NP lipid coatings allows today to introduce on the NP surface a large variety of lipid molecules eventually in mixture with amphiphilic or hydrophobic drugs or active molecules for cell targeting. In this review, the most relevant examples of NP lipid-coatings are presented and grouped in two main categories: supported lipid bilayers (SLB) and hybrid lipid bilayers (HLB). The discussed scientific cases take into account the most commonly used inorganic NP for biomedical applications in cancer therapy and diagnosis.